2010
DOI: 10.2459/jcm.0b013e32833e5687
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of surgical treatment of small aortic root with or without aortic root enlargement using a single prosthesis type

Abstract: ARE procedures are invaluable techniques in surgical management of small aortic root patients and can be used without significantly increasing early morbidity and mortality, particularly in those cases in which AVR with a small prosthesis will lead to severe PPM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…The JBI tool for non-randomised studies revealed a moderate risk of bias in 13 studies, 6,10,11,20,21,2326,2831 and a low risk of bias in one study. 27 Further details are mentioned in (Supplemental Table 2).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The JBI tool for non-randomised studies revealed a moderate risk of bias in 13 studies, 6,10,11,20,21,2326,2831 and a low risk of bias in one study. 27 Further details are mentioned in (Supplemental Table 2).…”
Section: Resultsmentioning
confidence: 98%
“…The most common pathology in patients with SV implants was aortic stenosis. Except for few studies 10,25,29 patients who had ARE, however, had combined diseases (both aortic stenosis and regurgitation).…”
Section: Resultsmentioning
confidence: 99%
“…Title and abstract screening were performed in duplicate, identifying 139 potentially eligible studies that underwent full-text review by two independent reviewers. Overall, 32 potentially eligible studies (12,13,20,21,(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51) were identified (52)(53)(54)(55)(56)(57)(58)(59)(60), including 17 studies (13,45-60) that were excluded because they did not include any information on at least one of the mid-term outcomes of interest through 5 years of followup. Consequently, 15 unique studies (12,20,21,(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44) remained and were included in data extraction and quantitative synthesis.…”
Section: Literature Searchmentioning
confidence: 99%
“…Some studies have reported acceptable results of aortic root enlargement (ARE) among young and middle-aged patients with SAA [5,6,11], whereas the outcomes remain controversial in elderly patients due to an elevated surgical risk. Additionally, stentless valves have been reported previously to lower the postoperative residual trans-aortic valve pressure [12][13][14], which has also been limited due to high technical requirements and undetermined long-term durability [4,[15][16][17].…”
Section: Introductionmentioning
confidence: 99%